2022
DOI: 10.3389/finsc.2022.957385
|View full text |Cite
|
Sign up to set email alerts
|

A numerical approach to investigating the mechanisms behind tonotopy in the bush-cricket inner-ear

Abstract: Bush-crickets (or katydids) have sophisticated and ultrasonic ears located in the tibia of their forelegs, with a working mechanism analogous to the mammalian auditory system. Their inner-ears are endowed with an easily accessible hearing organ, the crista acustica (CA), possessing a spatial organisation that allows for different frequencies to be processed at specific graded locations within the structure. Similar to the basilar membrane in the mammalian ear, the CA contains mechanosensory receptors which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Although poorly understood, katydid ears with reported AV might be endowed with a softer enclosure than the vertebrate cochlea. This enclosure is provided by the dorsal cuticle and surrounding structure such as the tympanal membranes, acoustic trachea and the colloidal material at each end of the inner ear cavity [15,27]. royalsocietypublishing.org/journal/rsif J. R. Soc.…”
Section: Inner Ear Liquid Compartmentalization and Biomechanical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although poorly understood, katydid ears with reported AV might be endowed with a softer enclosure than the vertebrate cochlea. This enclosure is provided by the dorsal cuticle and surrounding structure such as the tympanal membranes, acoustic trachea and the colloidal material at each end of the inner ear cavity [15,27]. royalsocietypublishing.org/journal/rsif J. R. Soc.…”
Section: Inner Ear Liquid Compartmentalization and Biomechanical Effectsmentioning
confidence: 99%
“…Based on anatomical studies of the hearing system of C. gorgonensis, Montealegre-Z et al [15] observed that the haemolymph channel in this species was not continuous as had been suggested before, but instead, they found a fluid trapped in a cavity bounded by the presence of a colloidal material at each end of the auditory organ. This cavity is the AV, and it is considered to be an important element of the auditory system as it provides a medium for the propagation of mechanical travelling waves and influences the dynamics of the tympanal membranes [19,27]. A fluid-filled cavity appears to be a required condition for the function of auditory organs in some Neotropical katydids.…”
Section: Introductionmentioning
confidence: 99%
“…The constructed STL files for the trachea geometries used in the numerical models (for six specimens) and the set-up of the three different numerical models (developed in COMSOL Multiphysics, v. 5.6) are available from the Dryad Digital Repository: [51].…”
Section: Data Accessibilitymentioning
confidence: 99%